Eigenvalue Problem for the Second Order Differential Equation with Nonlocal - Bandyrskii, B.; Lazurchak, I.; Makarov, V.; Sapagovas, M. (Nonlinear Analysis: Modelling and Control, 2006)
The paper deals with numerical methods for eigenvalue problem for the second order ordinary differential operator with variable coefficient subject to nonlocal integral condition. FD-method (functional-discrete method) is derived and analyzed for calculating of eigenvalues, particulary complex eigenvalues. The convergence of FD-method is proved. Finally numerical procedures are suggested and computational results are schown.
Keywords: eigenvalues; nonlocal condition; functional-discrete method; convergence; systems of symbolic mathematics